Reduction in Temperature-Dependent Fiber-Optic Gyroscope Bias Drift by Using Multifunctional Integrated Optical Chip Fabricated on Pre-Annealed LiNbO3 - Ercan Karagöz; Fatma Yasemin Aşık; Mutlu Gökkavas; Erkut Emin Akbaş; Aylin Yertutanol; Ekmel Özbay; Şadan Özcan (Photonics)
The refractive index change obtained after annealed proton exchange (APE) in lithium niobate (LiNbO3) crystals depends on both the proton exchange process carried out in hot acid and the structure of the crystals. In devices produced by the APE method, dislocations and lattice defects within the crystal structure are considered to be primary contributors to refractive index discontinuities and waveguide instability. In this study, the effects of pre-annealing LiNbO3 crystals at 500 °C on multifunctional integrated optical chips (MIOCs) were investigated through interferometric fiber-optic gyroscope (IFOG) system-level tests. It was observed that the pre-annealing process resulted in an improvement in the optical throughput of MIOCs (from %34 to %51) and the temperature-dependent bias drift stability of the IFOG (from 0.031–0.038°/h to 0.012–0.019°/h). The angle random walk (ARW) was measured as 0.0056 deg/√h.